Large-scale profiling of antibody reactivity to glycolipids in patients with Guillain-Barré syndrome - Thomma, RCM; Halstead, SK; de Koning, LC; Fehmi, J; Rinaldi, S; IGOS consortium (Oxford University Press, 2025)

(untitled)
Guillain-Barré syndrome is an acute polyradiculoneuropathy in which preceding infections often elicit the production of antibodies that target peripheral nerve antigens, principally gangliosides. Anti-ganglioside antibodies are thought to play a key role in the clinical diversity of the disease and can be helpful in clinical practice. Extensive research into clinical associations of individual anti-ganglioside antibody specificities has been performed. Recent research has highlighted glycolipid complexes, glycolipid combinations that may alter antibody binding, as targets. In this study, we investigated antibody reactivity patterns to glycolipids and glycolipid complexes using combinatorial array, in relation to clinical features in Guillain-Barré syndrome. In total, 1413 patients from the observational International Guillain-Barré syndrome Outcome Study (0-91 years, 60.3% male) and 1061 controls (healthy, family, infectious, vaccination, other neurological disease) were included. Acute-phase sera from patients were screened for IgM, IgG, and IgA reactivity against 15 glycolipids and one phospholipid and their heteromeric complexes, similarly to archived control sera. Antibody specificities and reactivity patterns were analysed in relation to clinical features. Of all patients, 1309 (92.6%) were positive for at least one anti-glycolipid (complex) antibody. Anti-GM1 and anti-GQ1b (complex) antibodies best distinguished motor GuillainBarré syndrome and Miller Fisher syndrome from controls, with antibodies to glycolipid complexes outperforming antibodies to single glycolipids. Three models consisting of antiglycolipid (complex) antibodies distinguished patients with Guillain-Barré syndrome, the motor variant, and Miller Fisher syndrome from controls with high sensitivity and specificity, performing better than antibodies to single glycolipids used in clinical practice. Seven patient clusters with particular antibody reactivity patterns were identified. These clusters were distinguished by geographical region, clinical variants, preceding Campylobacter jejuni infection, electrophysiological subtypes, the Medical Research Council sum score at study entry, and the ability to walk 10 meters unaided at 26 weeks. Two patient clusters with distinct anti-GM1 (complex) reactivity (broad versus restricted) differed in frequency of the axonal subtype. In cumulative incidence analyses, 15 anti-glycolipid (complex) antibodies were associated with the time required to regain the ability to walk 10 meters unaided. After adjustment for known prognostic factors, IgG anti-GQ1b:GM4, GQ1b:PS, and GQ1b:Sulphatide remained associated with faster recovery. Addition of anti-glycolipid antibodies to clinical prognostic models slightly improved their discriminative capacity, though insufficiently to improve the models. Measurement of anti-glycolipid antibodies by combinatorial array increases the diagnostic yield compared to assaying single glycolipids, identifies clinically relevant antibody reactivity patterns to glycolipids and glycolipid complexes, and may be useful in outcome prediction in Guillain-Barré syndrome.